Heads, Seekers, Psychonauts, and One-Timers: Patterns in Stories of Psychedelic Consumption - Dollar, Cindy Brooks (Journal of drug issues, 2023)
Psychedelics are psychoactive substances that alter ordinary states of consciousness. The U.S. criminalized ingestion of these drugs approximately 60 years ago and use remains punishable by law. Prior to this time, the substances were differentially declared spiritual sacraments, medicines, and/or party drugs. (Auto)Ethnographies and other research often indicate psychedelic-induced experiences as remarkably personal, necessitating subjective interpretation. Empirical studies exploring patterns across psychedelic encounters are rare, but among the few that exist, users tend to be identified as either pursuing psycho-spiritual enlightenment or self-indulgent amusement. The present paper utilizes narratives collected through 37 in-depth interviews with adults from diverse social backgrounds who report a history of psychedelic consumption in non-clinical settings. The data suggest a potential 4-part categorization based on five factors: named forms of psychedelic substances used, reported frequency of psychedelic ingestions, stated reasons for consumption and desistance, self-imposed rules surrounding use, and descriptions of drug effects and experiences.